Factors affecting subjective satisfaction with verbal communication among the disabled elderly and their family caregivers - Arai, Yumiko; Miura, Hiroko; Yamasaki, Kiyoko (Nihon Rōnen Igakkai zasshi, 2005)
The aims of the present study were to investigate satisfaction with verbal communication among the disabled elderly and their family caregivers; and to find the significantly influential factors of satisfaction with verbal communication. The subjects were 85 disabled elderly and 85 family caregivers. For the disabled elderly, satisfaction with verbal communication, demographic, and physical factors were examined using an interview survey. For the caregivers, satisfaction with verbal communication, demographic factors, and some factors related caregiving were examined using a self-administered questionnaire. In the disabled elderly, 82.4% were satisfied with their verbal communication while 55.3% of family caregivers were satisfied. Satisfaction with verbal communication between the disabled elderly and their caregivers showed low agreement (κ=0.17), Bivariate analysis revealed that satisfaction with verbal communication of the disabled elderly was significantly related to ADL (p<0.01), dysphagia risk (p<0.05), and ability of comprehension (p<0.05) while satisfaction with verbal communication of caregivers was significantly related to the gender of the disabled elderly and caregivers' burden. Furthermore, multiple regression analysis showed that the factor most related to satisfaction with verbal communication for the disabled elderly was ability of comprehension (p value=0.032, odds ratio=2.960), and the most related factor for their caregivers was the burden evaluated by J-ZBI_8 (p value=0.004, odds ratio=0.842). These results suggest that satisfaction with verbal communication of the disabled elderly disagrees with that of the family caregivers, and that some related factors for the disabled elderly are different from those in their family caregivers.